Narrativas de mulheres atendidas em avaliação terapêutica: uma análise feminista - Targino, Rebeca de Moura (2021)
Considering subjectivation as a process in continuous articulation with historical and social determinations consonant with the patriarchal capitalist mode of production, this study aimed to analyze, from a feminist perspective, phenomena expressed in the narratives of women assisted in Therapeutic Assessment processes (TA). Characterized as an interventional, collaborative and semi-structured process, TA is situated in this work as a useful space for the elaboration of narratives that are produced through social relations, with emphasis, for analytical purposes, on the resonances corresponding to social relations of sex. In accordance with the theoretical perspective adopted, namely, Socio-Historical Psychology, a methodology is proposed in line with historical-dialectical materialism, defined as a method of understanding reality that sees the existence of human beings within a historical context and in accordance with existing material relationships. An analysis was carried out of the audiovisual material corresponding to four TA processes, one of which was conducted with a retired teacher and the others related to teachers in the profession. The procedure for organizing and analyzing data was developed from three stages, starting with the floating observation of the material, followed by the construction of meaning cores, culminating in their analytical process. As a result, four central axes are presented, namely, Work: The place of the female teacher; Sexual division of work or “Giving what you don't have”; Control and Objectification of the female body; Affective (power) relationships. Such axes were built from the approximation of the different meaning cores extracted from the four TA processes, configuring themselves as a process that moved from the empirical to the interpretive field. The discussion of the axes was developed taking as a guideline the understanding of the historical and social determinations of gender relations, situated as structuring of the subjectivation process. The development of this study is highlighted as a possibility of contribution to two major areas, namely, Social Psychology and Psychological Assessment, highlighting the potential to articulate them with a view to expanding their respective knowledge.